Pengaruh Suhu Kalsinasi dan Waktu Kukus Terhadap Aktivasi Limbah Praktikum Isotherm Freundlich Di Laboratorium Kimia Analitik - Lasia, I Ketut; Wiratini, Ni Made (Al-Kimia, 2020)
This study aims to determine the effect of calcination temperature and steaming time on the activation of freundlich isotherm practicum waste (LPIF) in the Analytical Chemistry Laboratory. The LPIF was taken from the waste of the Physical Chemistry Practicum at the Analytical Chemistry Laboratory, Department of Chemistry, Ganesha University of Education. To achieve the research objectives, the LPIF was calcined at 165oC and 195oC, then steamed with 900 mL of distilled water at 400oC for 60 minutes and 45 minutes, respectively. The results of LPIF activation were characterized by absorption, increasing of absorption, FTIR spectrum, and SEM morphology. The results of the study showed that there were influences of calcination temperature and steaming time on LPIF in the Analytical Chemistry Laboratory. The best temperature of calcination and steaming time for activation of LPIF was calcination temperature of 195oC and steaming for 45 minutes.